Eksperimen Strategi Pembelajaran Kooperatif Tipe Group Investigation Dan Think Pair Share Ditinjau Dari Komunikasi Matematik Siswa Kelas VIII SMP Muhammadiyah 5 Surakarta - Ratna Sari, Yuna; , Dra. Nining Setyaningsih,M. Si (2017)
This research aims to examine (1) the influence of cooperative learning strategy Types Group Investigation (GI) and Think Pair Share (TPS) against the results of the learning of mathematics, (2) influences the level of mathematical communication students toward outcome studied mathematics, (3) the interaction of learning strategies and mathematical communication students toward outcome studied mathematics. Types of quantitative research with experimental design. Population penelitin the entire grade VIII Junior High School Muhammadiyah Surakarta with 5 sample research VIII grade-C and VIII-D. The technique of collecting data by the method of test and question form. Data analysis techniques using variansi analysis of two way cells do not match. Research results with α = 5% is (1) there was significant influence between the use of cooperative learning strategies Group-type Investigation and Think Pair Share against results of learning math students with FA = 4,256 > F0,05:1;63 = 3,99; (2) there was significant influence between the mathematical communication against the results of the study of mathematics students with FB = 4,317 > F0.05:2:63 = 3,14; and (3) there is no interaction between the mathematical communication and learning strategies of students toward outcome studied mathematics students with FAB = 0.966 > F0.05:2:63 = 3,1. Keywords: Group Investigation, Think Pair Share, Mathematical Communication, Mathematical Study Results